2022
DOI: 10.1007/s11356-022-19378-6
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of kinetin spraying strategy to alleviate the harmful effects of UVC stress on tomato plants

Abstract: Increasing ultraviolet (UV) radiation is causing oxidative stress that accounts for growth and yield losses in the present era of climate change. Plant hormones are useful tools for minimizing UV-induced oxidative stress in plants, but their putative roles in protecting tomato development under UVC remain unknown. Therefore, we investigated the underlying mechanism of pre-and post-kinetin (Kn) treatments on tomato plants under UVC stress. The best dose of Kn was screened in the preliminary experiments, and thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 102 publications
(110 reference statements)
1
8
0
Order By: Relevance
“…Bacteria can improve N 2 fixation, controlled by the nif gene and other basic genes; they can also improve plant growth, yield, soil nitrogen retention, and soil properties [ 108 ]. Photosynthesis, energy conservation, and carbon metabolism all need phosphate as a structural and signaling molecule [ 109 ]. As the cell’s principal osmoticum, potassium regulates cell expansion, plasma membrane potential and transport, pH value, and a variety of other catalytic activities [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria can improve N 2 fixation, controlled by the nif gene and other basic genes; they can also improve plant growth, yield, soil nitrogen retention, and soil properties [ 108 ]. Photosynthesis, energy conservation, and carbon metabolism all need phosphate as a structural and signaling molecule [ 109 ]. As the cell’s principal osmoticum, potassium regulates cell expansion, plasma membrane potential and transport, pH value, and a variety of other catalytic activities [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they claimed that tests on plant defense enzymes showed that polyphenol oxidase (PPO) activity was lower in vitro samples than it was in samples grown in soil. However, peroxidase (POX) activity was greater in plants (Dawood et al, 2022a).…”
Section: Discussion Discussion Discussionmentioning
confidence: 99%
“…Oxidative stress markers in the microalga Coccomyxa in response to CaO NPs were also addressed in the present work. Reactive oxygen species are generated in the thylakoid membrane during photosynthesis [85][86][87]. Hydrogen peroxide has been suggested to be the main species of ROS in algae.…”
Section: Physiological Responses Of C Chodatii To Different Levels Of...mentioning
confidence: 99%